The impact of pharmacist intervention on the use of activated vitamin D in a tertiary referral hospital in Malaysia - Siow, J.Y.; Lai, P.S.; Chua, S.S.; Chan, S.P. (Wiley, 2009)
OBJECTIVES: In recent years, the usage of activated vitamin D (alpha-calcidol and calcitriol) in the University Malaya Medical Centre (UMMC) has escalated and this has put unnecessary burden on the hospital's limited health care budget. The main aim of this study was to determine the effects of a clinical pharmacist's intervention in reducing the inappropriate use of activated vitamin D. METHODS: Data were collected retrospectively. Pre-intervention data were obtained from records of the previous year's use of activated vitamin D. An intervention screening form was developed based on a new guideline which was produced by the UMMC Osteoporosis Committee. Use of activated vitamin D from August 2006 to July 2007 was reviewed by a clinical pharmacist using the screening form. KEY FINDINGS: Of the 557 requests screened, 44.5 were identified as unnecessary prescriptions. The main indications recommended for prescribing activated vitamin D were long-term glucocorticoid treatment (38.8) and a bone mineral density T-score of less than -2.5 for patients aged 60 years and above (22.4). As a result of the intervention, the number of patients on activated vitamin D decreased from 4095 to 2338, which led to a significant reduction in expenditure from RM798 400.60 (US 221,777.90) to RM397 783.80 (110,495.50) (P = 0.002). The main reasons for the approval of activated vitamin D use were impaired renal function (46.6) and long-term glucocorticoid use (38.5). CONCLUSIONS: Pharmacist intervention on the use of activated vitamin D was effective and resulted in a cost saving of up to RM400 616.80 (111 282.40) annually. Prescribers in the UMMC are now aware of the guidelines and justifications for the use of activated vitamin D. Therefore, the implementation of the guidelines to reduce the inappropriate use of medications is a multidisciplinary effort between pharmacists and prescribers.